Women in Latin America and the Caribbean in the 1990s : diagnostic elements and proposals (UN SantiagoCL, 1997)
Explores the major changes that have influenced women's lives during the 1990s from a broad-based perspective as a means of helping to define activities whose implementation will extend beyand the year 2000.
Bibliography: p. 39-41